Implementasi Maqashid Syariah terhadap Pembiayaan Murabahah (Studi Kasus pada KSPPS BTM SUMBAR Cabang Pasar Raya) - Ummi Aini Al Gamis; Ali Rahman (ARZUSIN, 2026)
Although the implementation of maqashid syariah in murabahah financing has been widely studied in Islamic financial institutions, research specifically examining its application in addressing problematic murabahah financing in Sharia Savings and Loan and Financing Cooperatives (KSPPS) remains limited. This study aimed to analyze the implementation of maqashid syariah in murabahah financing at KSPPS BTM Sumbar Cabang Pasar Raya and identify the institution’s efforts to address problematic financing. The study employed a qualitative approach with a case study design. The research informants were selected through purposive sampling and consisted of the branch head, financing staff, and murabahah financing customers at KSPPS BTM Sumbar Cabang Pasar Raya. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that maqashid syariah was implemented through the cultivation of Islamic values, the execution of contracts in accordance with Sharia principles, financing feasibility analysis, and supervision of the use of financing funds. Nevertheless, the misuse of financing funds by some customers was still identified and contributed to problematic financing, indicating that the post-disbursement monitoring system needs to be strengthened. These findings contribute to the development of studies on maqashid syariah, particularly the aspect of hifz al-mal, in murabahah financing practices within Islamic microfinance institutions. This study emphasizes the importance of implementing the principle of hifz al-mal through responsible financing management, customer guidance, and continuous monitoring. In practical terms, the results provide implications for KSPPS in improving customer guidance and strengthening the financing monitoring system to minimize the risk of problematic financing.